The Disruption of Geniculocalcarine Tract in Occipital Neoplasm: A Diffusion Tensor Imaging Study - Yan Zhang; Sihai Wan; Ge Wen; Xuelin Zhang (Radiology Research and Practice)
Aim. Investigate the disruption of geniculocalcarine tract (GCT) in different occipital neoplasm by diffusion tensor imaging (DTI). Methods. Thirty-two subjects (44.1 ± 3.6 years) who had single occipital neoplasm (9 gliomas, 6 meningiomas, and 17 metastatic tumors) with ipsilateral GCT involved and thirty healthy subjects (39.2 ± 3.3 years) underwent conventional sequences scanning and diffusion tensor imaging by a 1.5T MR scanner. The diffusion-sensitive gradient direction is 13. Compare the fractional anisotropy (FA) and mean diffusivity (MD) values of healthy GCT with the corresponding values of GCT in peritumoral edema area. Perform diffusion tensor tractography (DTT) on GCT by the line propagation technique in all subjects. Results. The FA values of GCT in peritumoral edema area decreased (P=0.001) while the MD values increased (P=0.002) when compared with healthy subjects. There was no difference in the FA values across tumor types (P=0.114) while the MD values of GCT in the metastatic tumor group were higher than the other groups (P=0.001). GCTs were infiltrated in all the 9 gliomas cases, with displacement in 2 cases and disruption in 7 cases. GCTs were displaced in 6 meningiomas cases. GCTs were displaced in all the 7 metastatic cases, with disruption in 7 cases. Conclusions. DTI represents valid markers for evaluating GCT’s disruption in occipital neoplasm. The disruption of GCT varies according to the properties of neoplasm.